ANALYSIS OF BUSINESS FEASIBILITY STUDY ON QUATTORDICI SCREEN PRINTING BUSINESS REVIEWED FROM MARKETING, FINANCE AND HUMAN RESOURCES ASPECTS - Afrilzal, Afril Zal; Garini, Anggita Riastina; Anjani, Dinda Dewi; Lestari, Putri Ayu; Ken, R.R, Wening (Universitas Muhammadiyah Tangerang, 2024)
The Indonesian lifestyle is developing along with economic globalization and the proliferation of shopping centers, especially the fashion industry such as the screen printing business. This business is still in the early stages of development, so there are three main considerations: aspects related to marketing, aspects related to finance, and aspects related to human resources. The purpose of this research is to determine the business feasibility of the Quattordici screen printing company. Quattordici's screen printing business was the subject of this kind of qualitative research. Interview and observation techniques are used in data collection techniques. Qualitative descriptions are used in data analysis. The research results show that the three perspectives consisting of promotion, finance and HR in the quattordici screen printing business are expected to be implemented.